STUDI KASUS KEMAMPUAN LITERASI ANAK YANG DAPAT MENULIS TETAPI BELUM BISA MEMBACA DI TK AISYAH 28 - Devi Novita Yuniar Astutik; Muchamad Arif (MOTORIC, 2026)
This study aims to describe the literacy skills of early childhood children who can write but not yet read at Aisyiyah 28 Kindergarten. This phenomenon is interesting to study because it shows an imbalance between writing and reading skills in early childhood. The child who is the focus of the study has been able to write letters of the alphabet, copy simple words, and write his own name, but still has difficulty in recognizing letter sounds, reading simple words, and understanding the meaning of the words he writes. This study uses a qualitative approach with a single case study type. The subject of the study was a preschool child at Aisyiyah 28 Kindergarten who was selected purposively because he showed the characteristics of being able to write but not yet able to read. Data collection techniques were carried out through participatory observation, semi-structured interviews with teachers and parents, and documentation in the form of writing results, development notes, and the child's literacy portfolio. Data were analyzed qualitatively through the process of data reduction, data grouping, theme arrangement, interpretation, and drawing conclusions. The results of the initial study showed that children's writing skills developed first because children were more often stimulated by activities such as copying letters, writing names, and imitating word forms. Conversely, reading skills have not developed optimally because children are still limited in recognizing the relationship between letters, sounds, and word meaning. Factors suspected of influencing this condition include literacy stimulation that emphasizes writing activities, limited sound-based reading activities, and the need for support appropriate to the child's cognitive developmental stage. This research is expected to provide insight into the importance of balancing reading and writing activities in early literacy learning for young children. Keywords: early literacy, early reading, early writing, early childhood, case study